2020
DOI: 10.1111/tbed.13697
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Japanese encephalitis virus in mosquitoes from Xinjiang during next‐generation sequencing arboviral surveillance

Abstract: Japanese encephalitis virus (JEV) is arguably the most important acute viral encephalitis in the world (Campbell et al., 2011), with an estimated 68,000 clinical cases, and 10,000-15,000 associated deaths per year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…JEV is a single-stranded, positive-sense RNA virus and is phylogenetically classified into five genotypes (genotype I to V) according to the nucleotide sequence of the E gene. Most isolates from JEV hosts belong to genotype I (GI) or genotype III (GIII) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…JEV is a single-stranded, positive-sense RNA virus and is phylogenetically classified into five genotypes (genotype I to V) according to the nucleotide sequence of the E gene. Most isolates from JEV hosts belong to genotype I (GI) or genotype III (GIII) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We further examined the seroprevalence of JEV during different months and seasons of the year in 2019–2020. From June to September, the environmental conditions are conducive for mosquitos’ growth in Shanghai, and it is also the epidemic period of JE [ 46 , 47 , 48 ]. We observed that the average JEV-antibody-positive ratio was 16.4% during spring (March to May), which was substantially below the average positive rate of JEV antibodies in the epidemic late autumn (46.3%) and winter seasons (35.7%) ( p < 0.05) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach can also be used for the rapid identification of new vector species, the feeding sources and the screening for arboviruses, allowing the surveillance of potential emerging viruses and the prevention and control of VBDs (Batovska et al 2018). When applied to the whole body, midgut, salivary glands or expectorated saliva samples of haematophagous arthropods that feed on the blood of several vertebrate hosts, including mammals and birds, this strategy contributes to vector incrimination in enzootic, endemic and epidemic transmission cycles and to the assessment of the risk for the human population (Batson et al 2021;Birnberg et al 2020;Brinkmann et al 2016;Charles et al 2018;Grubaugh et al 2015;Hameed et al 2021;Russell et al 2018;Xiao et al 2018;Yang et al 2015).…”
Section: Metagenomic Ngs For the Identification And Discovery Of New ...mentioning
confidence: 99%